ความหลากหลายของไลเคน ณ โป่งน้ำร้อนท่าปาย อำเภอปาย จังหวัดแม่ฮ่องสอน - จีนะเจริญ ศรัณย์; ยารังสี คัทลียา; คบพิมาย ยุพเยาว์ (Thai Journal of Science and Technology, 2020)
The survey of lichen diversity in the area of Tha Pai hot spring, Pai District, Mae Hong Son was performed in eight lines outward from the centre of the hot spring. Ten trees in each line with every five metres in distance (80 trees in total) were marked. The grid frame 10 x 50 cm2 was placed on the bark. The photos of lichen were taken. Lichen morphology and physical characters, tree perimeter, bark type and direction of tree, which the most lichen abundance were recorded. The results showed that there were 24 families and 38 genera of the lichens. Two families and three genera were in foliose group and 22 families and 35 genera were in crustose. The relationship between numbers of lichen thallus and bark type showed that three genera, Lepraria, Pertusaria and Pyrenula, were found no significant difference on both smooth and rough bark (p = 0.328, 0.365 and 0.262, respectively). On the other hand, there were seven genera showed the existence on a smooth bark more than a rough bark, which were Arthopyrenia, Bacidia, Cryptothecia, Graphis, Letrouitia, Malmidea and Opegrapha (p < 0.05). There was one genus, Diploschistes, which was found on a rough bark more than a smooth bark (p = 0.005). Lichen was mostly found on the north of tree stem. The correlations between the distance from the hot spring and the numbers of genus and thallus were very low, R2 = 0.1163 and 0.0655, respectively. Moreover, the average numbers of genus in each survey line were similar (p = 0.598). In addition, one genus (Pamotrema) which was categorized to be sensitive to air quality, and 11 genera which were categorized to be tolerant and highly tolerant to air quality, were found in this study.